2020
DOI: 10.1038/s41574-020-0392-2
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–glucose cotransporter type 2 inhibitors for the treatment of type 2 diabetes mellitus

Abstract: The management of type 2 diabetes mellitus (T2DM) is becoming increasingly complex. Sodium-glucose cotransporter type 2 inhibitors (SGLT2is) are the newest antidiabetic agents for T2DM. By targeting the kidney, they have a unique mechanism of action, which results in enhanced glucosuria, osmotic diuresis and natriuresis, thereby improving glucose control with a limited risk of hypoglycaemia and exerting additional positive effects such as weight loss and the lowering of blood pressure. Several outcome studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(134 citation statements)
references
References 251 publications
(389 reference statements)
5
118
1
10
Order By: Relevance
“…The most frequent AEs for henagliflozin were ketosis‐related events, which could be expected from the metabolic shift towards lipids and ketone bodies as energy fuel resulting from increased urine glucose excretion by the drug 25 . Importantly, most cases of ketosis were mild, with no case of DKA observed in our study, consistent with the low occurrence rate of DKA documented for other SGLT2 inhibitors 19 . The incidence of urinary tract infections was generally low and similar across the henagliflozin and placebo groups, consistent with a meta‐analysis of 86 randomized trials reporting that the risk of urinary tract infections was not increased with SGLT2 inhibitors compared with placebo or active control 26 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The most frequent AEs for henagliflozin were ketosis‐related events, which could be expected from the metabolic shift towards lipids and ketone bodies as energy fuel resulting from increased urine glucose excretion by the drug 25 . Importantly, most cases of ketosis were mild, with no case of DKA observed in our study, consistent with the low occurrence rate of DKA documented for other SGLT2 inhibitors 19 . The incidence of urinary tract infections was generally low and similar across the henagliflozin and placebo groups, consistent with a meta‐analysis of 86 randomized trials reporting that the risk of urinary tract infections was not increased with SGLT2 inhibitors compared with placebo or active control 26 .…”
Section: Discussionsupporting
confidence: 88%
“…25 Importantly, most cases of ketosis were mild, with no case of DKA observed in our study, consistent with the low occurrence rate of DKA documented for other SGLT2 inhibitors. 19 The incidence of urinary tract infections was generally low and similar across the henagliflozin and placebo groups, consistent with a meta-analysis of 86 randomized trials reporting that the risk of urinary tract infections was not increased with SGLT2 inhibitors compared with placebo or active control. 26 Notably, the incidence of genital infections, a common AE reported for SGLT2 inhibitors, was also low (<2%) across all treatment groups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The chronic hyperglycemic state contributes to oxidative stress by increasing levels of AGEs and ROS (46), increasing the risk of development of microvascular (retinopathy, nephropathy, and neuropathy), and macrovascular complications (congestive heart failure, stroke, coronary heart disease, myocardial infarction, and peripheral vascular disease) (42,47). These consequences result in a reduction in quality of life and life expectancy by even ten years among diabetic patients (42,48).…”
Section: Discussion Type II Diabetes Mellitus In a Nutshellmentioning
confidence: 99%
“…Diabetes is a serious chronic metabolic disorder affecting 463 million of individuals worldwide in 2019, and a further 700 million likely to be added by 2045 1 . Additionally, numerous epidemiological studies have shown that diabetes is not only closely related to blindness, limb amputations, and renal failure, but also an independent risk factor for peripheral artery disease [2][3][4] . Indeed, diabetes can be categorized into two types: T1D is mainly caused by insu cient insulin secretion, and T2D is abnormal insulin secretion and/or non-insulin-dependent diabetes, complicated by postprandial hyperglycemia 5,6 .…”
Section: Introductionmentioning
confidence: 99%